LEGAL RESPONSIBILITY OF PERPETRAL VIOLATIONS OF THE HANDLED ETLE SYSTEM USING VEHICLES - M. Habib Kevin Setiyawan; Yalid; Olivia Anggi Johar (JILPR Journal Indonesia Law and Policy Review, 2026)
This study aims to analyze the legal liability of traffic violators through the Handled ETLE system who use vehicles under someone else's name, the obstacles faced, and efforts to overcome them. The study uses a normative legal method. The results show that law enforcement through Handled ETLE is carried out in stages, starting from violation detection, recording electronic evidence, verification, vehicle identification, sending confirmation letters, clarification, issuing e-tickets, and settlement through payment of fines. If the vehicle owner does not provide confirmation, they may be subject to administrative sanctions in the form of temporary blocking of the vehicle registration certificate (STNK). Legal liability remains borne by the driver who committed the violation, while the vehicle owner is only obliged to provide clarification regarding the driver's identity. The Handled ETLE system applies the principle of liability based on fault and supports legal certainty, justice, transparency, and accountability in traffic law enforcement.